Antimicrobial Utilization in a Rural Children’s Hospital of South India - Rathinavelu, Mohanraj; Ganesan, Veeramani; Jyothi, Mallela Vijaya (Indian Journal of Pharmaceutical Education and Research, 2025)
Background The “more-is-better” antimicrobial prescribing philosophy besides resistance is a significant contributor to suffering and death in children. Only a few nations have given comprehensive and comparable statistics on pediatric antimicrobial usage. However, such pediatric research is scarce in India, which necessitates antimicrobial pharmaco-surveillance. Materials and Methods The retrospective antimicrobial drug use study was conducted in a rural children’s hospital of south India. The antimicrobial pediatric prescription was investigated using WHO/INRUD prescribing indicators and classified according to the WHO ATC index. The antimicrobial use was calculated by using DDD and its deviation if any to prescribed daily dose was determined. Results Pneumonia was the most common illness and the main reason for hospitalization in 38% of infants and toddlers. A total of 79.66% antimicrobial agents were administered intravenously. Ceftriaxone (n=40, 33.9%) was the commonly used antimicrobial agent, with a PDD:DDD value of 0.84. Conclusion The pediatric antimicrobial utilization was adequately studied which found no discrepancies, but on contrary it was observed that prescribing practices was not consistent with WHO core prescribing indicators. This necessitates the implementation of pediatric antimicrobial stewardship programs.
Keywords: Antimicrobials; ATC/DDD Index; Drug Utilization; Observational Studies